Effect of ambient temperature on competence of deer ticks as hosts for Lyme disease spirochetes. - Shih, C M (1995)
We determined whether the temperature of extrinsic incubation affects the competence of vector ticks as hosts for Lyme disease spirochetes (Borrelia burgdorferi). Larval Ixodes dammini ticks that had engorged on spirochete-infected C3H mice were incubated continuously at various temperatures, and the gut contents of the resulting nymphs were examined for spirochetes by direct immunofluorescence microscopy. Spirochetes were present in virtually all nymphs kept at 27 degrees C or less for 6 months, in only 10% of those kept at 33 degrees C, and in none kept at 37 degrees C. Spirochetes became undetectable within 8 weeks when nymphs were warmed from 27 to 33 degrees C beginning at the time of molting. Nymphs became virtually noninfective for mice after incubation at temperatures higher than 27 degrees C for 2 weeks or longer. We conclude that ambient temperatures in excess of 27 degrees C are not permissive for transmission of the agent of Lyme disease.